2010
DOI: 10.1136/ip.2009.021766
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychosocial risk factors for musculoskeletal disorders in New Zealand nurses, postal workers and office workers

Abstract: In injury prevention and rehabilitation the physical nature of the work needs to be addressed for most MSDs, with modest decreases in risk seemingly possible. Addressing job strain could provide significant benefit for those with neck and wrist/hand pain, while the effects of somatisation and the promotion of good mental health may provide smaller but global benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 31 publications
(27 reference statements)
7
62
4
11
Order By: Relevance
“…This study finding is also supported by Sheikhzadeh's study on work related musculoskeletal disorder [12]. Walker et al [13] conducted a study in 2000 which showed that low back pain is the most common back pain with a point prevalence of 12-33% and the life time prevalence estimated to be 11 to 84% and the annul prevalence of LBP was 22-65% respectively [13].…”
Section: Discussionsupporting
confidence: 60%
“…This study finding is also supported by Sheikhzadeh's study on work related musculoskeletal disorder [12]. Walker et al [13] conducted a study in 2000 which showed that low back pain is the most common back pain with a point prevalence of 12-33% and the life time prevalence estimated to be 11 to 84% and the annul prevalence of LBP was 22-65% respectively [13].…”
Section: Discussionsupporting
confidence: 60%
“…In a number of studies therefore, investigators have studied 'neck and/or shoulder' disorders, even though there may be important differences in risk factors for pain in the neck region as opposed to those for the shoulder [39]. Neck pain is a very common symptom, with an estimated annual cumulative incidence of 17.9% [40] and a lifetime prevalence of 71% [41].…”
Section: Neck/shoulder Disordersmentioning
confidence: 99%
“…About 30 % of all LBDs are work-related (8), including psychosocial factors such as job strain (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%